Use of Intelligent Agents to Facilitate Group Learner Participation in Collaborative mLearning - Njenga, Stephen T.; Oboko, Robert O.; Omwenga, Elijah I. (International Journal of Computing Sciences Research, 2018)
Purpose – Learning Management Systems (LMS) provide a platform for collaborative learning with features such as online group discussions. Grouping members together to participate in a group discussion does not guarantee their participation in the online discussion. However, the use of intelligent agents to facilitate group participation can motivate group members to participate in the online group discussions leading to improved levels of group knowledge construction. This paper discusses an experimental design for evaluating facilitated learner participation in online group discussions using intelligent agents. Method – In our experimental design we use two treatment groups (turn taking and informative feedback group facilitations) and one control group. We compared the levels of group knowledge construction amongst the three groups. Results – The results of the study show improved levels of group knowledge construction where the facilitations for participation were provided compared to where they were not provided. Conclusion – The study concluded that facilitating collaborative mobile learning using intelligent agents improves the levels of group knowledge construction. Recommendation – Thus, we recommend the use of intelligent agents in facilitating group participation and consequently improving the group knowledge construction in collaborative mobile learning environments. Practical Implication – The study implies that intelligent agents are effective in collecting and analysing group processes leading to improved interactions which improve group knowledge construction.